2022
DOI: 10.1021/acscatal.2c01241
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Iridate Nanosheets with a Highly Active and Stable Layered Perovskite Framework for Acidic Oxygen Evolution

Abstract: Ir-based perovskite oxides show great promise for next-generation oxygen evolution reaction (OER) electrocatalysts in an acidic medium, but they are generally stuck with their uncontrollable surface amorphization and thus structural instability (e.g., serious Ir leaching) during OER. Herein, we report the high-yield chemical exfoliation of Ruddlesden–Popper layered perovskite Sr2IrO4 into protonated colloidal nanosheets with an undamaged perovskite framework. We further demonstrate the potential of protonated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…25 In order to tackle this problem, layered perovskite iridate (e.g., Ruddlesden−Popper phase Sr 2 IrO 4 , Figure 1c) is later found to have higher OER activity than SrIrO 3 , 26,27 with crystalline H 4 IrO 4 as the final catalytic active phase. 28 Even with these progresses, there is still large room for improvement in the structural stability of highly active iridate electrocatalysts, and there is still a lack of sufficient understanding about the relationship between crystal structures and structural stability of iridate electrocatalysts. Herein, we report, for the first time, honeycomb layered strontium iridate (SrIr 2 O 6 ) as a highly efficient and stable electrocatalyst for acidic OER.…”
Section: Introductionmentioning
confidence: 99%
“…25 In order to tackle this problem, layered perovskite iridate (e.g., Ruddlesden−Popper phase Sr 2 IrO 4 , Figure 1c) is later found to have higher OER activity than SrIrO 3 , 26,27 with crystalline H 4 IrO 4 as the final catalytic active phase. 28 Even with these progresses, there is still large room for improvement in the structural stability of highly active iridate electrocatalysts, and there is still a lack of sufficient understanding about the relationship between crystal structures and structural stability of iridate electrocatalysts. Herein, we report, for the first time, honeycomb layered strontium iridate (SrIr 2 O 6 ) as a highly efficient and stable electrocatalyst for acidic OER.…”
Section: Introductionmentioning
confidence: 99%
“…With further research on superwetting materials, it is found that the superwetting interface has a special three-phase contact area and controllable microfluidic characteristics, which can manipulate the transport of liquid, [13][14][15] gas, 16,17 and ions. [18][19][20] Researchers have applied the special mass transfer performance to various chemical reactions to control the adsorption of reactants and desorption of products, so as to improve reaction efficiency, such as electrochemical reactions, [21][22][23][24] photocatalytic reactions, 25,26 bioelectronic reactions, 27 and organic synthesis reactions. [28][29][30][31] However, the research in chemical reactions is still in early stage, the depth and breadth of research are far from enough, especially for the heterogeneous organic chemical reactions with huge systems and various types.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of O (II‑δ)– (electrophilic lattice oxygen) species in Ca 2 Y 0.2 Ir 0.8 O 4 is highly conducive for the enhanced OER activity by lowering kinetic barriers due to an energetically favorable *OO– formation process during acidic OER . The amount of lattice oxygen in IrO 2 and some A 2 IrO 4 (for example, Sr 2 IrO 4 ) directly participating in acidic OER is negligible . The other three new peaks in the O K -edge XANES spectrum of Ca 2 Y 0.2 Ir 0.8 O 4 after 20 cycles (Figure S12) are from the adsorbed Ca­(ClO 4 ) 2 on the surface of Ca 2 Y 0.2 Ir 0.8 O 4 due to the Ca leaching during acidic OER in HClO 4 solution.…”
mentioning
confidence: 98%
“…26 The amount of lattice oxygen in IrO 2 and some A 2 IrO 4 (for example, Sr 2 IrO 4 ) directly participating in acidic OER is negligible. 34 1000 cycles show that there is no obvious amorphous layer on the surface (Figure S14). The leached Ir from Ca 2 Y 0.2 Ir 0.8 O 4 after 1000 cycles is only 0.95 wt% of the total Ir (Figure S15).…”
mentioning
confidence: 99%